2018
DOI: 10.1111/nph.15395
|View full text |Cite
|
Sign up to set email alerts
|

On the minimum leaf conductance: its role in models of plant water use, and ecological and environmental controls

Abstract: Contents Summary I. Introduction II. Comparison of various definitions and measurement techniques of minimum conductance III. Cuticular conductance IV. Contribution of stomata V. Environmental and ecological variation in minimum conductance VI. Use of minimum conductance in models VII. Conclusions Acknowledgements References SUMMARY: When the rate of photosynthesis is greatly diminished, such as during severe drought, extreme temperature or low light, it seems advantageous for plants to close stomata and compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
302
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(356 citation statements)
references
References 100 publications
(237 reference statements)
19
302
6
1
Order By: Relevance
“…By contrast, plant desiccation time was unrelated to the minimum conductance of individual leaves g min . This is consistent with previous work suggesting g min is highly responsive to growth conditions (Duursma et al ., ), although some studies have shown the adaptive value of low g min with respect to drought tolerance (Burghardt & Riederer, ; Brodribb et al ., ). Plant desiccation time was also unrelated to the RWC at g s90 and Ψ crit , and somewhat unexpectedly was unrelated to the span of RWC between these thresholds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, plant desiccation time was unrelated to the minimum conductance of individual leaves g min . This is consistent with previous work suggesting g min is highly responsive to growth conditions (Duursma et al ., ), although some studies have shown the adaptive value of low g min with respect to drought tolerance (Burghardt & Riederer, ; Brodribb et al ., ). Plant desiccation time was also unrelated to the RWC at g s90 and Ψ crit , and somewhat unexpectedly was unrelated to the span of RWC between these thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…During drought, plants typically close their stomata as a first response to minimize water loss (Martin-StPaul et al, 2017;Li et al, 2018a). However, if drought persists, tension within the water-conducting xylem will increase as plants dehydrate via water loss through permeable leaf cuticles and leaky stomata (Kerstiens, 1996;Brodribb et al, 2014;Schuster et al, 2017;Duursma et al, 2019). Without relief, increasing xylem tension can cause cavitation and widespread embolism (air bubbles that block water transport), leading to hydraulic dysfunction and plant death (Tyree & Sperry, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Slope is set 13 for herbaceous vegetation and 9.5 for woody vegetation, respectively (Miner et al, ) (Miner et al, ). Intercept is set 0.01 umol·m −2 ·s −1 (Duursma et al, ) with a multiplicative water stress factor RHVPD/1000.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, our analysis indicates that day-length regulation may be particularly important as affecting minimal conductance (g 0 ). There has been a large body of literature trying to understand the meaning of this parameter (see review by Duursma et al, 2019), as well as its drivers, and here we show, for the first time to our knowledge, that it could vary seasonally with photoperiod. Our results also hint that, in conifers, day-length responses could mediate the slope of stomatal models (g 1 ), but the generality of this claim remains to be tested because in the available dataset from the literature, there were only four conifer species.…”
Section: Can These Results Be Extrapolated To Other Woody Species?mentioning
confidence: 56%